Levels of hypoxanthine phosphoribosyltransferase RNA in human cells - Steen, Ann-Marie; Luthman, Holger; Hellgren, Dennis; Lambert, Bo (EXPERIMENTAL CELL RESEARCH, 1990)
The gene for the purine salvage enzyme hypoxanthine phosphoribosyltransferase (HPRT) is expressed at a low level in many cells. As is the case with several other “housekeeping genes,” thorough studies of hprt gene regulation have been hampered by the low levels of its mRNA. We have used RNA/RNA hybridization in solution to determine the concentration of hprt-RNA in human cells. The sensitivity and specificity of the method have been validated, and it is shown that hprt-RNA can be accurately determined at a level of a few mRNA molecules per cell. As expected for a housekeeping gene, low and relatively constant hprt-RNA levels (0.3–0.8 pg/μg DNA) were found in primary cultures of normal amnion cells and fibroblasts, EBV-transformed lymphoblastoid cell lines, neuroblastoma, glioblastoma, and melanoma cell cultures. While resting lymphocytes were found to contain very low amounts of hprt-RNA, lymphocytes stimulated with phytohemagglutinin (PHA) showed a 10-fold increase to about 0.8–1.2 pg/μg DNA, which corresponds to 6–10 hprt-RNA molecules per cell. The level started to increase about 20 h after PHA stimulation, 5–10 h before the onset of DNA synthesis, and a steady-state level was reached after 2–3 days in culture. In PHA-stimulated lymphocytes from two brothers with inherited HPRT deficiency (LeschNyhans syndrome), the hprt-RNA level in PHA-stimulated lymphocytes was only about 25% of that in normal subjects. In T-cells selected for HPRT deficiency by growth in 6-thioguanine medium, the levels of hprt-RNA were either normal or very low, which probably reflects the different nature of the mutations involved. These results demonstrate the sensitivity of this method for determinations of low levels of RNA and clearly show induction of hprt-RNA after mitogenic stimulation of human lymphocytes.